Humic acid and indigenous microbe treatments for better yield of pak choy grown in dairy farm effluent compost - Edelisa Jenny Radius; Chong, Khim Phin; Yap, Yun Fook; Jupikely James Silip; Januarius Gobilik (Faculty of Science and Natural Resources, 2021)
The consumption of Pak Choy in Malaysia is higher than the local production. This vegetable has to be imported to meet the demand. The present study was carried out to investigate the effect of humic acid (HA) and indigenous microbe formulation (IMF) on the growth and yield of Curly Dwarf Pak Choy (CDP) grown in 100 % dairy farm effluent compost (DFEC). DFEC was sterilized and added or not added with HA, IMF or NPK 15: 15: 15. The vegetable was planted in 18 L pots. The treatments were applied following a completely randomized design of three replicates with three CDP per replicate. Data were collected for growth (plant height, leaf number, leaf area, and root length) and yield (fresh and dry matter weights). Addition of HA or IMF alone or in combination did not increase the growth and yield significantly. Yield was better only when HA + IMF was added with NPK where the CDP achieved 63.98 g fresh weight/plant (52.40 g/pot). HA+IMF appears to increase nutrient uptake. HA+IMF is recommended for farmers to use together with NPK to improve Pak Choy production.